Analysis of UMKM Product Design Using Digital Marketing for UMKM in Jambenenggang Village (KKM Group 8) - Yepi Sopian; Imas; Siti Silvia Sari; Siti Rokayah; Risa Tarisa Chairunnisa; Risma Noviyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service was carried out at one of the UMKM in Jambenenggang village, Kebonpedes sub-district, Sukabumi district. This service is carried out with the aim that the Jambenenggang village UMKM can master digital marketing. Because this can be seen from the many micro and small business products that exist, but it is difficult to compete with other products that are marketed in online buying and selling media. This activity also aims to help UMKM owners in marketing their products. In this era, as an economic actor, you must be able to analyze SWOT (Strength, Weakness, Opportunity and Treatment). In addition to other products that are competitors, especially with products that are sold the same which are definitely competitors, there are also competitors whose strength is certainly greater, namely technology that is already sophisticated in this era of globalization. So with that, KKM group 8 conducted digital marketing training for Mrs. Ira, mentoring and creating social media accounts, making branding or brand labels for dry seblak products